2021
DOI: 10.1155/2021/8419415
|View full text |Cite
|
Sign up to set email alerts
|

Polymethoxyflavones in Citrus Regulate Lipopolysaccharide‐Induced Oscillating Decay of Circadian Rhythm Genes by Inhibiting Nlrp3 Expression

Abstract: The aim of this study is to compare the regulatory abilities of citrus flavonoids on the oscillating expression of circadian genes. Seven varieties of citrus fruits and twenty-five citrus flavonoids were selected and evaluated. Per2 luciferase bioluminescence report system and serum shock were used to induce circadian gene expression in mouse microglia BV-2 cells. In vivo experiments were carried out using C57BL6/J mice to evaluate the regulation of flavonoids on the oscillatory expression of liver biorhythm g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The studies included in this review were published from 2008 to 2024, with the majority published after 2016, reflecting the growing scientific interest in (poly)phenols and circadian biology. Table 2 [ [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] ] summarizes the main characteristics and outcomes of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included in this review were published from 2008 to 2024, with the majority published after 2016, reflecting the growing scientific interest in (poly)phenols and circadian biology. Table 2 [ [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] ] summarizes the main characteristics and outcomes of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“… Wang et al. [ 87 ], 2021 7 Citrus fruit extracts 6 N/A Mouse BV-2 2-h Serum shock (50% horse serum) Pretreatment citrus flavonoid extracts or NOB/12 h and then 0.1 μg/mL LPS/12 h. Control (0.05% DMSO) and LPS Per2 luciferase reporter system knock-in (PER2::Luc) Almost all flavonoid extracts ↑ PER2 mRNA Nobiletin (NOB) 10 ↑ CLOCK, BMAL1, PER1/2/3, CRY1/2, Rev-Erbα/β, RORα, DBP, and NPAS2 mRNAs Okada and Okada [ 95 ], 2020 Resveratrol (Res) 100 Human lung fibroblast cells (TIG-1-20, young cells; and TIG-1-60, old cells) None Treatment with Res/4 h. Control (0.1% DMSO). ↑ BMAL1 mRNAs in both types of fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also found that citrus flavonoids could induce cellular antioxidant activity by inhibiting the ubiquitination of Nrf2 (Wang et al., 2021b). PMFs in citrus could reverse LPS‐induced circadian rhythm disturbance in mouse liver by inhibiting Nlrp3 inflammasome formation (Wang et al., 2021c). The biological activities of flavonoids are closely related to their molecular structures.…”
Section: Introduction Of Flavonoids and The Uniqueness Of Citrus Flav...mentioning
confidence: 99%